Information Theory and the Role of Intermediaries in Corporate Governance - Reinhard H. Schmidt; Marcel Tyrell (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2004)
We investigate the connection between corporate governance system configurations and the role of intermediaries in the respective systems from a informational perspective. Building on the economics of information we show that it is meaningful to distinguish between internalisation and externalisation as two fundamentally different ways of dealing with information in corporate governance systems. This lays the groundwork for a description of two types of corporate governance systems, i.e. insider control system and outsider control system, in which we focus on the distinctive role of intermediaries in the production and use of information. It will be argued that internalisation is the prevailing mode of information processing in insider control system while externalisation dominates in outsider control system. We also discuss shortly the interrelations between the prevailing corporate governance system and types of activities or industry structures supported.
Keywords: P51; L21; G34; D83; D82; D23; 330; Economics of information; corporate governance; financial systems; complementarity; Corporate Governance; Informationsökonomik; Informationsverbreitung; Finanzintermediär; Theorie